OPTIMASI SUBTITUSI BEKATUL PADA PEMBUATAN NASI JAGUNG INSTAN - Puspitojati, Endah (Jurnal Ilmu-Ilmu Pertanian, 2015)
The easiness of rice processing is a challenge for the processed instant corn rice so the consumers can easily cook corn rice. In order to increase value added of corn rice as functional food, then rice bran can be added. The aims of this research were to determine the optimal composition of rice bran substitution in the production of instant rice bran- corn rice and to determine the characteristic of instant rice bran-corn rice. This research used Respond Surface Methods (Design Expert 9 Programs) which obtained 13 running formula. The formula provided an optimal solution at 0,900 level of desirability which treatment amount of rice brand by 9% and no soaking treatment. According to solution of program, resulted the characteristic of instant rice bran - corn rice with water content 2.58%, bulk density 45.9 %, porosity 87.3%, development volume 254% dan water absorption 206%.